2021
DOI: 10.1186/s12888-021-03145-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of depression and associated factors among elderly people in Womberma District, north-west, Ethiopia

Abstract: Background Depression is a common mental disorder that suffers many elderly people who are neglected, their problems are overlooked, and no efforts are made to mitigate their suffering. It is a mental health problem which is both underdiagnosed and under treated in primary care settings. This study was aimed to assess the prevalence and associated factors of depression among elderly people in Womberma District, Ethiopia. Methods A community based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
2
27
1
Order By: Relevance
“…Another study conducted with elderly living alone revealed a positive correlation between depressive symptoms and self-neglect [3]. Elderly with depressive symptoms tends to have lower life expectations, loss of interest or pleasure in activities and sense of hopelessness [24], all of which may increase their risk for self-neglect. Not surprisingly, higher levels of depression also signi cantly predict higher suicidal ideation among disability elderly [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted with elderly living alone revealed a positive correlation between depressive symptoms and self-neglect [3]. Elderly with depressive symptoms tends to have lower life expectations, loss of interest or pleasure in activities and sense of hopelessness [24], all of which may increase their risk for self-neglect. Not surprisingly, higher levels of depression also signi cantly predict higher suicidal ideation among disability elderly [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study finding was higher than study done in North Indian (9.5%) [ 11 ], Malaysian (16.5%) [ 3 ], Tanzania 21.2% [ 17 ], a systematic review conducted in China (38.6%) [ 19 ], Thailand (18.5%) [ 20 ], Ambo, Ethiopia (41.8%) [ 21 ], Singapore 13.4% [ 14 ], China 32.8% [ 16 ], and Womberma district, Ethiopia (45%) [ 9 ]. This variation might be due to social-cultural, economic disparities, and the heterogeneity in the classification of depression, i.e., they utilized a GDS-15 score of 6 and above to define depression, which could lead to an underestimating of depression prevalence in Chinan [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to numerous studies showed, the prevalence of depression in older adults (aged 60 and above) in Chitradurga was 60% [ 8 ], while in Womberma District, Ethiopia, it was 45%. [ 9 ] South Africa 40% [ 10 ], North Indians 9.5% [ 11 ], Vietnam 6.9% [ 12 ], Egypt 44.4% [ 13 ], Malaysia systematic 16.5% [ 3 ], Singapore [ 14 ] 13.4%, Ethiopia (Harer) 28.5% [ 15 ], Ambo 41.8%, Chinese tertiary hospital 32.8% [ 16 ], Tanzania 21.2% [ 17 ], Greece 58.5% [ 18 ], systematic review conducted in Asian countries 38.6% [ 19 ] and Thailand 18.5% [ 20 ]. Suicide risk is higher among older adults when they are depressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of senior citizens living alone is increasing, few researchers have identified factors related to the characteristics of depression in these individuals by using epidemiological survey data representative of this population group. Although epidemiological surveys on the prevalence of depression in the senile stage have been actively conducted in many countries[ 10 - 13 ], the prevalence of depression varied between them due to differences in the survey sampling methods, depression testing tools, and evaluation methodology. Researchers usually use two-phase designs in psychiatric epidemiological studies to classify subjects into a depression-positive group and a depression-negative group quickly and economically by using a simple standardized screening test in the first phase followed by conducting a robust diagnostic test in the second phase to save on the labor and economic burden[ 14 ].…”
Section: Introductionmentioning
confidence: 99%